DIGITAL CONTENT MARKETING CONCEPT WITH PERSONAL CUSTOMER EXPERIENCE APPROACH ON RABBITHOLEID INSTAGRAM - Ekadyasa, Sartika; Patrissia, Ressa Uli (Politeknik Negeri Media Kreatif, 2024)
In the middle of customers' growing mistrust of traditional advertising, firms need extremely efficient substitutes for traditional marketing communications. Under these circumstances, digital content marketing (DCM) is gaining prominence on a worldwide scale and is rapidly being recognized as a crucial element in organizations' marketing plans, serving as a supplementary tool to traditional marketing methods. Digital content marketing involves the forming and dissemination of interesting, pertinent, and captivating material by organizations to their intended audience using digital platforms. The research aims to see beyond the notion on marketing using qualitative method by examining the discourse and content of Rabbithole.id's digital material. It focuses specifically on the personal customer experience approach, which has gotten little attention from communication and marketing academics too far. The result finds that DCM is critical in attracting customers, as seen by Rabbithole.id's creation of emotionally resonant material that uses brilliant colors and contains wisdom, factual information, and positive affirmations. Furthermore, we anticipate that each comment will get a response, recognition, and the incorporation of engaging components to increase their audiences. The results also show that periodically analyzing the importance of digital content marketing while utilizing the data gathered to improve content offerings has a favorable impact on content marketing efficacy. Findings and results have the potential to make significant theoretical advances in digital content marketing academically and to increase practitioners' abilities to maximize the design and execution of digital content marketing campaigns. Keyword:social media content, digital contentmarketing, personal customerexperience, Instagram